Lanthanide-activated single-phosphor white light emission via Bi3+ → Eu3+ energy transfer in Ca2Ga2GeO7 for next-generation LEDs - Chethana, K. N.; Kanojiya, Nitesh S.; T.Parayil, Reshmi; Sreevalsa, S.; Das, Subrata; Mishra, Manish Kumar; Gupta, Santosh K. (Materials Letters, 2026)
{We report the design and fabrication of Bi3+ and Eu3+ co-doped Ca2Ga2GeO7 (CGGO) phosphors for highperformance warm-white light-emitting diodes (LEDs). The phosphor exhibits efficient Bi3+ -> Eu3+ energy transfer, as evidenced by spectral overlap, enhanced Eu3+ emission, and quenching of Bi3+ emission with increasing Eu3+ content. The emission color shifts from blue to red with increasing Eu3+, achieving near-white emission at 3% Eu3+ (x = 0.33
Keywords: Bi3+/Eu3+ co-doping; Ca2Ga2GeO7 phosphors; Energy Transfer; UV-excited LEDs; White light emission